Neuropsychological Impairment in Prodromal, First-Episode, and Chronic Psychosis: Assessing RBANS Performance. - TianHong Zhang; HuiJun Li; William S Stone; Kristen A Woodberry; Larry J Seidman; YingYing Tang; Qian Guo; KaiMing Zhuo; ZhenYing Qian; HuiRu Cui; YiKang Zhu; LiJuan Jiang; et al. (PLoS ONE, 2015)
Cognitive deficits are observed throughout all developmental phases of psychosis. However, prior studies have usually focused on a limited illness period and used a wide variety of cognitive instruments. Therefore, it has been difficult to characterize or highlight cognitive functioning in different stages of psychosis.We administered the RBANS (Repeatable Battery for the Assessment of Neuropsychological Status) tests to 4 participant subgroups, including healthy volunteers (controls, HC, n = 28), subjects at high risk for clinical psychosis (prodrome, CHR, n = 27), first-episode schizophrenia patients (FE-Sz, n = 26), and mid-term and long-term chronic schizophrenia patients (Ch-Sz, n =147). Comparison, correlation, and regression analyses of RBANS index scores were assessed among groups. We examined clinical outcomes over 2 years between the CHR and HC subjects, and RBANS domains were used as possible predictors for conversion to psychosis.Performance on all RBANS domains was significantly impaired during a post-onset stage of psychosis (FE-Sz and Ch-Sz), and RBANS scores declined along with disease progression. Regression analyses showed that for CHR and HC subjects, baseline impairment in delayed memory (DM) significantly predicted conversion to psychosis. Additionally, partial correlations showed that for FE-Sz and Ch-Sz subjects, DM was the only correlate with a later stage of psychosis.Cognitive deficits broadly emerged, and diminished functioning followed along with disease progression. Impairment in DM is perhaps one domain that helps us understand the development of psychosis. A critical need is to monitor and treat memory functioning for psychotic patients throughout all phases of the disease.